Peningkatan Hasil Belajar Peserta Didik Kelas VII SMP Negeri 1 Pakkat Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) Pada Materi Kemampuanku Berkembang dan Keterbatasan yang Kusyukuri - Petronelta Katarina Sitanggang; Timotius Tote Jelahu; Modestus Haryono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of grade VII students of Junior High School (SMP) Negeri 1 Pakkat in the subject of Catholic Religious Education and Character Education through the application of the Problem-Based Learning (PBL) model. The type of research is classroom action research which is carried out in two cycle stages. Each cycle consists of several activities, namely planning, implementation, observation, and reflection. Data collection techniques use two techniques, namely the main and supporting techniques. The main technique uses the observation method and written tests in the form of summative assessments, while the supporting techniques are in the form of questionnaires, interviews, and documentation. The data obtained are analyzed descriptively. The results of the study show several things as follows: (a) the application of the Problem Based Learning (PBL) learning model in learning the material my abilities are developing. (b) the application of the Problem Based Learning (PBL) learning model in learning the material my abilities are developing and the limitations I am grateful for can improve the learning outcomes of grade VII-5 students, this is indicated by an increase in the results of observations in cycle I with an average score of 77 to 85 in cycle II, and cognitive learning outcomes increased from an average score of 79 to 87 in cycle II. which is 81 in cycle I increased to 89 in cycle II. (c) Student learning outcomes after the implementation of the Problem Based Learning (PBL) learning model reached the KKTP as expected with proficient and competent, but the average learning outcomes showed the proficient category. The conclusion of this study is that the implementation of the Problem Based Learning (PBL) learning model can improve the learning outcomes of Catholic Religious Education and Character Education of class VII-5 students of SMP Negeri 1 Pakkat.